The Correlation of Snack Consumption and Physical Activity Between Nutritional Status in University Students - Aliya, Donna Nathania; Pratama, Satwika Arya (MEDIKORA, 2024)
The nutritional status of adolescents is a problem that requires special attention because it has a significant impact on their growth and physical development as adults. Possible nutritional problems that can occur in students include malnutrition, anemia (iron deficiency), obesity and other micronutrient deficiencies. This research uses quantitative research and a cross-sectional research design with the dependent variable, nutritional status. Meanwhile, the independent variables, namely snack consumption intake and physical activity, were analyzed univariately and bivariately using the Pearson test. The results of this study show that the relationship between consumption of energy, protein, fat and carbohydrate snacks is not related to nutritional status with a value of p>0.05. Meanwhile, the results of the relationship between physical activity were not related to nutritional status with a p value of >0.05. Students at the Faculty of Engineering, Surabaya State University are advised to control the food they consume by choosing nutritious food and doing regular physical activity such as exercising and taking a leisurely walk.